PENGGUNAAN MODEL THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) DALAM MENGANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI LAJU REAKSI - Lestari, Darliana; Yenti, Elvi (Journal of Chemistry Education and Integration, 2024)
AbstractProblem-solving ability was one of abilities that should be owned by students, and this ability was on low category in Indonesia. It needed attention to be developed because of the successful indicators of chemistry learning process. This research aimed at knowing how student problem-solving ability achievement on 4 problem-solving indicators after being taught by using Thinking Aloud Pair Problem Solving (TAPPS) model on Reaction Rate lesson. The subjects of this research were the eleventh-grade students of MIPA 4 at State Senior High School 1 Kampar, and Purposive sampling technique was used in this research. It was a quantitative descriptive research. The design used in this research was the one-shot case study. The data analysis result showed that problem-solving ability of students taught by using TAPPS model on 4 problem-solving indicators had various percentages. The achievement of problem-solving indicator on the indicator of planning the plans was 82.64% (very good), the indicator of implementing the plans was 78.52% (good), the indicator of crosschecking was 69.95% (good), and the indicator of understanding the problems was 63.32% (good). So, it was obtained that the mean of problem-solving ability of all the eleventh-grade students of MIPA 4 at State Senior High School 1 Kampar was 73.60%, and it was on good category.Keywords: Thinking Aloud Pair Problem Solving (TAPPS), Problem-Solving, Reaction Rate